2022
DOI: 10.3390/ijerph191912673
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Quality and Functional and Conventional Ratios of Trunk Strength in Young Healthy Subjects: A Pilot Study

Abstract: Background: The trunk strength conventional ratio (CR) has been evaluated. However, the functional ratio and the ratio of strength to body weight (BW) or muscle mass (MM) have been poorly explored. Relative strength is a measure of muscle quality. Objectives: To analyze the trunk strength ratio normalized by BW and MM and compare the trunk’s conventional and functional ratios collected in isokinetic and isometric conditions. Methods: Twenty-seven healthy males (21.48 ± 2.08 years, 70.22 ± 7.65 kg) were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Nowadays, an increasing number of authors are investigating the use of these devices and the standardization of tests and training protocols [26,34]. In our case, although this is the first study that evaluates the reliability of the FEMD during the performance of a squat, the reliability of other exercises in the different working modes of the FEMD has also been evaluated in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, an increasing number of authors are investigating the use of these devices and the standardization of tests and training protocols [26,34]. In our case, although this is the first study that evaluates the reliability of the FEMD during the performance of a squat, the reliability of other exercises in the different working modes of the FEMD has also been evaluated in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the described antecedents, it has been evidenced that an increase in muscular strength decreases psychosocial variables [ 12 , 19 , 45 ]. In this context, it is understood that a higher level of strength would generate a higher MQI [ 20 22 , 43 ]. Therefore, there should be a direct and inverse relationship between MQI and psychosocial variables.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a direct relationship between muscle strength and the muscle quality index (MQI) has been demonstrated, and it has been determined that a low level of strength will trigger a poor MQI [20][21][22]. Likewise, it has been shown that MQI is also influenced by high subcutaneous adipose tissue content and high-fat percentages, with an inverse relationship between MQI and fat tissue [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that the use of specific strength assessment tests, the FDST, together with field tests, the SPT, is useful for the trainer or researcher to know the operational status of the athlete at a given time without deviating too much from the specific preparation objective, since these tests are suitable to evaluate and improve performance at the same time. In this research, FDSTs could be applied thanks to the use of the DEMF, a new device that allows evaluating and training strength in natural conditions [34,[47][48][49][50].…”
Section: Practical Applicationsmentioning
confidence: 99%